Visual Ethnography and its Applications in Ethnographic Painting - Yakup, Mohd Rafee; Awangko Hamdan, Awang Arshad; Abdul Riezal, Dim; Hishamuddin, Siri; Mohd Jefri, Samaroon (Elsevier Ltd., 2015)
This paper argued that Visual Ethnography could be used as an alternative in the production of Visual Arts. The researcher suggested that various Visual Arts composition could be engaged in enhancing the quality of Visual Ethnography images and be part of the Ethnographic Painting. The discussion was established from the biography of the cultural object of Pagan Melanau, bilum. Then, the relationship between Social Science and Visual Arts were observable within the context of academic research after the analysis process was clarified. The approach was enlightened through the visual studies and production of two paintings in establishing the employed method.